2018
DOI: 10.1371/journal.pntd.0006159
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of attendance to dog rabies static point vaccination clinics in Blantyre, Malawi

Abstract: Rabies is a devastating yet preventable disease that causes around 59,000 human deaths annually. Almost all human rabies cases are caused by bites from rabies-infected dogs. A large proportion of these cases occur in Sub Saharan Africa (SSA). Annual vaccination of at least 70% of the dog population is recommended by the World Health Organisation in order to eliminate rabies. However, achieving such high vaccination coverage has proven challenging, especially in low resource settings. Despite being logistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 29 publications
4
70
1
1
Order By: Relevance
“…The Mission Rabies and University of Edinburgh partnership has explored the reasons why vaccination coverage remains suboptimal when relying solely on static points (Mazeri et al . ). We have found that distance from static point is critical with increasing distance from home to static point resulting in lower vaccination coverage.…”
Section: Vaccination Strategiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The Mission Rabies and University of Edinburgh partnership has explored the reasons why vaccination coverage remains suboptimal when relying solely on static points (Mazeri et al . ). We have found that distance from static point is critical with increasing distance from home to static point resulting in lower vaccination coverage.…”
Section: Vaccination Strategiesmentioning
confidence: 97%
“…In addition, reasons such as lack of knowledge about the vaccination campaign, difficulty in handling dogs and concerns about suitability of young dogs for vaccination were also commonly cited reasons as to why dogs were not presented for vaccination at static point clinics (Mazeri et al . ). This information will be informative when shaping future vaccination programmes in this region.…”
Section: Vaccination Strategiesmentioning
confidence: 97%
“…Lanka. In a similar study using the same technique for a campaign in Malawi, Mazeri et al [10] found that there was a decreasing likelihood of attending a SP with increasing distance from home to said SP, in dogs of young age, and animals with poor health. These results parallel the findings from the Negombo study.…”
Section: Identification Of Barriers Of Attendance To Spmentioning
confidence: 97%
“…Static point (SP) vaccination approaches are commonly used, as they are easy to establish and are an efficient way to vaccinate a large number of dogs with limited personnel. However, reliance on SP clinics only often leads to a failure to vaccinate a sufficient proportion of the population, since they depend on high ownership levels and other socio-economic and cultural factors which may influence dog owners' attendance [10]. Although more logistically challenging and costly, "door-to-door" (D2D) approaches based on visiting all households in a community and vaccinating free-roaming and owned dogs are able to achieve high coverages very effectively [11,12].…”
mentioning
confidence: 99%
“…Notwithstanding these limitations, we found that transects were fast and relatively low cost to complete at scale, sampling populations more representatively than other approaches that were limited in spatial scope. We suggest that transects should be completed immediately after vaccination campaigns, aiming to cover the center and the periphery of villages, as vaccination coverage has been reported to decrease with the distance to the vaccination point [17,22,50,51], and that estimates should be adjusted to account for not observing pups.…”
Section: Prediction Of Dog Population Sizes and Densitiesmentioning
confidence: 99%